Impact of feeding habits of Corsican red deer (Cervus elaphus corsicanus) on vegetation at Quenza Park in Corsica - Maillard, D; Casanova, J B; Gaillard, J M (MAMMALIA, 1995)
Following the translocation of Corsican red deer (Cervus elaphus corsicanus) in Quenza enclosures in 1985, we tried to assess the impact of red deer on woody mediterranean species. We found that sempervirent species with persistent leaves like Calytcotome villosa, Arbutus unedo, Quercus ilex and Cistus salviaefolius were eaten by deer all the year along. In fact, we identified three different categories of plant species according to the different levels of use by deer. A first groupe includes species highly and quickly consumed by deer like Calycotome villosa, Fraxinus ornus and Lonicera etrusca. These plants can even disappear when deer density becomes very high. A second group was composed of plant species red deer ate but searched for in a lesser extent like Arbutus unedo and Quercus ilex. Consumption of some of them showed a peak during summer (Rosa canina and Rubus sp.). in the last groupe, we pooled species weakly consumed by red deer, like Erica arborea and Cistus salviaefolius.
APS
Keywords: Arbutus unedo; Calytcotome villosa; Cervus elaphus corsicanus; Cistus salviaefolius; comsumption; Mediterranean; Quercus ilex; red deer

Notas sobre el comportamiento de Cistus salviaefolius tras desbroces, laboreos, fertilizaciones y aplicación de fitocidas - Montoya Oliver, J M; Montero González, G (Pastos, 1977)
The Cistus salviaefolius L. is an invading and competitive species in the pastures of Quercus súber covered mounts. In order to control it we carried out some triáis of (1) rotary cutting, (2) rotary cutting -+- ploughing and (3) rotary cutting + ploughing -+- fer- tilizing, under Q. súber trees that covered 40 % aind (4) rota'ry cutting in 25 % shade: The inventory of the number of plants shows according to the comparative plots which did not undertake any treatment at all, that the reinvasion is fast and very intense. In triáis with phytocides before emergence (atrazine, simazine, bromacil and diuron) the results of control of Cistus were not as good as the ones we got in the comparative plots that were just ploughed; and besides that they produced a lack of pasture for nearly two years. The phytocides did not damage the Q. súber when using those dosis. Those results have improved the knowledge of how meteorological factors could affect the germination abi'lity of Cistus salviaefolius, that could be useful for the coming studies directed to its control. 246
Keywords: Cistus salviaefolius; desbroce; fertilización; fitocidas (voyant); laboreo